2021
DOI: 10.1177/2050313x211054623
|View full text |Cite
|
Sign up to set email alerts
|

A case of primary tracheal squamous cell carcinoma arising from malignant transformation of recurrent respiratory papillomatosis, with a complete response to concurrent chemoradiotherapy

Abstract: Recurrent respiratory papillomatosis is a human papillomavirus-mediated condition characterised by the development of benign squamous papillomata of the respiratory tract. Malignant transformation of recurrent respiratory papillomatosis, while rare, carries a poor prognosis and there are limited data surrounding treatment options, particularly in inoperable disease. We present the case of a 64-year-old male who developed malignant airway obstruction secondary to primary tracheal squamous cell carcinoma in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In our study, the majority (71.4%) of the CCRT group patients received cisplatin-based chemotherapy, as in other studies [15,18,27]. Videtic et al reported a case in which a patient with unresectable disease achieved a complete response after receiving cisplatin based CCRT, maintaining a disease-free status at the two-year follow-up [22].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, the majority (71.4%) of the CCRT group patients received cisplatin-based chemotherapy, as in other studies [15,18,27]. Videtic et al reported a case in which a patient with unresectable disease achieved a complete response after receiving cisplatin based CCRT, maintaining a disease-free status at the two-year follow-up [22].…”
Section: Discussionsupporting
confidence: 79%
“…Our current study revealed a tendency towards improved PFS and OS when concurrent chemotherapy was administered alongside RT, indicating that CCRT may be an effective treatment option for patients who are not eligible for surgery. Some hospital data-based studies and case reports have reported clinical outcomes of patients undergoing CCRT, but without systematic statistical analysis, while one study using the National Cancer Database found superior median OS for CCRT compared to RT alone (Supplementary Table 5) [14][15][16][17][18][19][20][21][22]. Therefore, to our knowledge, this is the rst clinical report comparing CCRT with RT alone and demonstrating the bene ts of CCRT exclusively in patients with squamous cell carcinoma among tracheobronchial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we report the case of a 69‐year‐old woman who had juvenile‐onset RRP with partial malignant transformation in the trachea that was refractory to surgical treatment, and complete remission was achieved by low‐dose cisplatin combined with de‐escalated radiotherapy. Despite there are several reports regarding the effectiveness of cisplatin against squamous cell carcinoma that transformed from RRP, 4,5 data on low‐dose cisplatin‐based chemoradiotherapy for refractory benign RRP are quite rare. Although cytoreductive therapy should not be aggressively recommended because RRP are benign tumors, our experience reinforces the opinion that low‐dose cisplatin combined with de‐escalated radiotherapy can be an effective and safe treatment alternative for uncontrollable and lethal RRP.…”
Section: Discussionmentioning
confidence: 99%